Siagai Laggek: Pengetahuan Tumbuhan Obat Oleh Penyembuh Sebagai Obat Tradisional di Kepulauan Mentawai - Andreas Rino Sitanggang (Universitas Tanjungpura, 2022)
In the Mentawai community there are also shamans who can provide treatment to sick people who are usually called Sikerei. Treatment is usually done by performing a series of ceremonies, so that the evil spirit that causes the disease can be coaxed out of the human body. Usually, those who act as medical experts in the Mentawai are Sikerei who generally come from men. In fact, in Mentawai, especially on the eastern coast of southern Siberut, this healing ability is not only possessed by the Sikerei. The ability to heal the sick turns out that many people in local terms are called Siagai Laggek, even Simatak. These Siagai Laggek alerts are still an alternative for the community to get medical assistance or to obtain healing if someone gets an illness.The method used is qualitative and data collection techniques in the form of observation, interviews and literature study. The purpose of this study is to describe the types of medicinal plants and their use as healers to treat diseases suffered by the Mentawai people.The results show that there are 46 types of medicinal plants used by Siagai Laggek to treat diseases with naturalistic and personalistic disease classifications. The knowledge gained is based on the Arat Sabulungan which interacts between nature, humans and rulers (divine spirit). So that knowledge about medicinal plants used by Siagai Laggek as traditional medicine is based on culture.